2009
DOI: 10.1080/16066350902770458
|View full text |Cite
|
Sign up to set email alerts
|

How do people recover from alcohol dependence? A systematic review of the research on mechanisms of behavior change in Alcoholics Anonymous

Abstract: Rigorous reviews of the science on the effectiveness of Alcoholics Anonymous (AA) indicate that AA and related 12-step treatment are at least as helpful as other intervention approaches. Exactly how AA achieves these beneficial outcomes is less well understood, yet, greater elucidation of AA's mechanisms could inform our understanding of addiction recovery and the timing and content of alcohol-related interventions. Empirical studies examining AA's mechanisms were located from searches in Pubmed, Medline, Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(175 citation statements)
references
References 105 publications
(128 reference statements)
7
161
0
7
Order By: Relevance
“…Such studies that have performed appropriate mediational tests (see MacKinnon, 2008) have found that measures of coping, motivation, self-efficacy, social network changes, and spirituality appear to be some of the mechanisms through which AA transmits its beneficial effects (Forceheimes and Tonigan, 2008;Kelly et al, 2009). However, to our knowledge, important affectrelated mechanisms that AA itself specifies as critical to recovery have not been formally tested.…”
Section: Role Of Anger In Alcoholics Anonymous's Recovery Programmentioning
confidence: 99%
“…Such studies that have performed appropriate mediational tests (see MacKinnon, 2008) have found that measures of coping, motivation, self-efficacy, social network changes, and spirituality appear to be some of the mechanisms through which AA transmits its beneficial effects (Forceheimes and Tonigan, 2008;Kelly et al, 2009). However, to our knowledge, important affectrelated mechanisms that AA itself specifies as critical to recovery have not been formally tested.…”
Section: Role Of Anger In Alcoholics Anonymous's Recovery Programmentioning
confidence: 99%
“…G. E. Vaillant [8] pažymi, jog anoniminiai alkoholikai atranda džiaugsmą padėdami kitiems, o dalyvavimas 12 žingsnių programoje prisideda prie ilgalaikio depresijos mažinimo. J. F. Kelly et al [9] nurodo, kad daž-nesnis anoniminių alkoholikų grupių lankymas susijęs su geresnėmis alkoholio vartojimo pasekmėmis ir depresijos mažėjimu. A. Kolbergytė ir V. Indrašienė [10] nurodo, kad žmonių dalyvavimas savitarpio pagalbos grupėse gerina jų emocinę būseną, jie išmoksta "gyventi su savo problema".…”
Section: Rezultatų Aptarimasunclassified
“…Se acepta con bastante frecuencia que afrontar con éxi-to situaciones de alto riesgo de recaída es sustancial para el proceso de cambio en las adicciones, 1 además de ser uno de los mecanismos que se facilitan con la asistencia a los grupos de AA. [15][16][17] Un elemento central en AA es el reforzamiento de la abstinencia, mediante el "ayudar a otros a recuperarse del alcoholismo". 18 Los testimonios en las reuniones y el apadrinamiento son los mecanismos clave de tal ayuda y por medio de los cuales se aprenden y modelan las conductas de recuperación.…”
Section: Antecedentesunclassified